Bentuk Gharar Dalam Jual Beli Biji Kopi Ditinjau Dalam Hukum Islam - Abu Huroirah Pasaribu & Muhammad Arsad Nasution & Dermina Dalimunthe (Jurnal El-Thawalib, 2021)
The problems in this thesis are how is the form of gharar in the sale and purchase of coffee beans in BatangParsuluman Village, SaiparDolok Hole District, SouthTapanuli Regency and How is Islamic Law Review on the form of gharar in coffee bean buying and selling transactions in BatangParsuluman Village, SaiparDolok Hole District, South Tapanuli Regency. The purpose of this research is to determine the sale and purchase transactions of coffee beans in BatangParsuluman Village, SaiparDolok Hole District, SouthTapanuli Regency and to find out the Islamic Law Review on coffee bean buying and selling transactions in BatangParsuluman Village, SaiparDolok Hole District, South Tapanuli Regency. This research is field research. Sources of data in this study are primary data and secondary data. Data collection techniques using field studies, namely observation, interviews, documentation and literature study. Interviews were conducted by coffee buyers, coffee sellers, religious leaders, and community leaders in BatangParsuluman Village, SaiparDolok Hole District, SouthTapanuli Regency. The data processing and data analysis techniques of this research are after the data has been collected, the next step is to conduct data analysis processing. The results of this study indicate that the form of gharar in the sale and purchase of coffee beans in Batang Parsuluman Village, Saipar Dolok Hole District, South Tapanuli Regency is: buying and selling of goods that are not clear about their nature, affects the results of coffee milling so that it is not completely good and many are destroyed. The practice of buying and selling coffee has fulfilled the terms of sale and purchase and the terms of sale and purchase. However, the practice of buying and selling coffee does not meet the legal requirements of buying and selling. Which is the legal requirements for buying and selling must be avoided from harming one of the parties, one of which is to avoid gharar. The law that does not have text is the sale and purchase of coffee, where coffee sold by coffee farmers has not been dried in the sun, even some that have not been ripe but have already been added. in the sack to be sold to the second shop. can't be seen because it's still in the sack.